$T$-differentiable functionals and ther critical points - Mel'nik, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The critical points of the functionals $F:\; D \subset X \rightarrow \mathbb{R}$ defined on "nonlinear" sets $D$ in the topological vector spaces $X$ are studied. A construction of a $T$-derivative is suggested for these functionals and compared with to known constructions. The concept of a weak critical point is introduced and Coleman's principle is justified for $T$-differentiable functionals.